Peran Produser pada Program Feature Televisi â€œGeliat Budaya Ngopi di Pontianakâ€ - Maulid, Faiz Iqbal; Sarifah, Siti; Anggraeni, Tri (Jurnal Ilmiah Multimedia dan Komunikasi, 2023)
Pontianak has a great business potential in the coffee sector and eventually makes it as the largest coffee exporting city in Indonesia. Then this is an interesting theme to be made into a feature format of television program. This program will especially attract more to urban people who want to know more about simple activities that affect the level of happiness in Indonesia. This scientific work discusses the role of the producer in making a feature program titled "Geliat Budaya Ngopi di Pontianak" which contains a feature format with the theme of human interest, as well as informative and entertaining feature program. The creation of this program went through pre-production, production and post-production stages. Producer plays an important role in the content of a program. Producer is required to take concern and combine the elements in planning, producing, and broadcasting a television program in order to get high quality production results. These elements include production materials, production facilities, production costs, human resource management, as well as the stages of production implementation. This feature program combines several sub-formats such as vox pop, statements, and narratives that support the information and visuals.